The Magnificent Emperor Wu : China's Han Dynasty - Hung, Hing Ming (Algora Publishing, 2020)
"One of the greatest emperors in Chinese history, Liu Che (157 BC-87 BC) is known posthumously as Emperor Wu. Under his reign China expanded its territory dramatically. Liu Che consolidated China's power under a strong central government founded on Confucian principles. This book, based largely on the writings of China's ancient historian, Sima Qian, summarizes the development of the Han Dynasty and the reign of Emperor Wu"--